Computing the temporal intervals by making a Throne-Morris wormhole from a Kerr black hole in the context of f(R,T) gravity - Harikant, Aruna; Singha Roy, Sanjeevan; Bhattacharjee, Deep (International Journal of Scientific Research and Management (IJSRM), 2021)
In the paper we will proceed towards taking the larger root of  and make it equal to zero to remove the event horizon of a Kerr black hole (BH) in Boyer-Lindquist coordinates with a prevalent ring type singularity that can be smoothen by a tunneling approach of a spherinder thereby proceeding safely towards the Cauchy horizon with the deduced intervals computed in detail for the time travel in the Throne-Morris wormhole (WH) approach under  gravity without the presence of any exotic matter at the WH mouth thereby preserving the asymptotically solutions of flaring out conditions and mouth opening during the course of the journey through the Einstein-Rosen bridge. An approach has been organized in the paper in which not only time travel is possible without exotic matter but also time travel is flexible to past and future in the Einstein’s universe by eliminating all sorts of paradoxes by spatial sheath through 2D approach of temporal dimensions.